Vasculitides in HIV-infected children: a case series & literature review - Dempoulos, Despina (My University, 2012)
Medium and large vessel vasculopathy in HIV-infected patients is an uncommon but important cause of mortality and morbidity in both adult and paediatric patients. The estimated frequency in children from the current literature is 1-2%. The overall HIV prevalence among children 18 years of age and younger in South Africa is currently 2.9%. This series reports on medium and large vessel vasculopathy in children with HIV. Six HIV infected children seen at three Johannesburg hospitals between 2000 -2006, are described, all presenting with complications arising from medium and/or large vessel involvement. Additional cases are reviewed from the literature. A description of the clinical presentation, radiological investigations, the possible aetiology, pathophysiology and management of these patients is presented. The case series and literature review compares HIV vasculopathy and Takayasu’s arteritis. Both entities can present with multiple aneurysms and a diagnosis of tuberculosis, thus a possible link in the pathogenesis is explored. Most patients with HIV vasculopathy present while severely immunosuppressed. However, some patients in the case series and literature review present despite adequate viral suppression, suggesting the possibility of an immune-reconstitution inflammatory syndrome in the pathogenesis of this vascular complication. Medical management and in selected cases, surgery, has been used in the management of patients with HIV vasculopathy. The outcomes thus far are good.
M.Med.(Paediatrics), Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: Vasculitis; HIV Infections--complications